YTHDF2 Inhibits Gastric Cancer Cell Growth by Regulating FOXC2 Signaling Pathway - Shen, Xudong; Zhao, Kui; Xu, Liming; Cheng, Guilian; Zhu, Jianhong; Gan, Lei; Wu, Yongyou; Zhuang, Zhixiang (Frontiers in Genetics, 2021)
Background: Gastric cancer (GC) is one of the most common malignancies in the world, and the fourth most frequent malignancy worldwide. YTHDF2 (YTH domain family 2, YTHDF2) binds to mRNA containing m6A, thereby regulating the localization and stability of the bound mRNA. YTHDF2 was shown to be associated with some cancer patient prognosis. However, the effect of YTHDF2 on in Gastric cancer and the molecular mechanism of this effect have not been documented. Methods: Analysis of YTHDF2 expression levels in public databases and gastric cancer patient samples. The effects of YTHDF2 on the growth of gastric cancer cells were detected in vivo and in vitro. RNA-seq analyzes the signal pathways regulated by YTHDF2, and makes experiments to verify. Results: In our study, we found that YTHDF2 has lower expression in GC tissues and GC cells, and inhibits the growth of GC cells. In addition, the analysis of clinical data found that the expression level of YTHDF2 is closely related to the stage of GC and the survival of patients with GC. RNA sequencing results showed that overexpression of YTHDF2 significantly reduced protein expression in the FOXC2 (Forkhead box protein C2, FOXC2) signaling pathway. Finally, we found that knockout of FOXC2 reversed the inhibitory effect of YTHDF2 on GC cells. Conclusions: In summary, YTHDF2 inhibits the growth of GC cells by negatively regulating FOXC2 and may as a prognostic marker in GC.